KONTRIBUSI PERAN PENDIDIK ASRAMA TERHADAP PEMBENTUKAN RANAH AFEKTIF SANTRI: ANALISIS KUANTITATIF DI PONDOK PESANTREN DINIYYAH PUTRI LAMPUNG - Fadila Rahmah; Imam Syafe'i; Bambang Sri Anggoro (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The development of the affective domain is a central objective of Islamic boarding school education, as it reflects the internalization of values, religious attitudes, and moral character among students. Dormitory educators play a strategic role in this process through consistent modeling, supervision, religious guidance, and socio-emotional support within daily residential life. This study aims to analyze the contribution of dormitory educators to the development of students’ affective domain at Diniyyah Putri Islamic Boarding School, Lampung. A quantitative approach with a correlational design was employed. A total of 237 students were selected using proportional stratified random sampling. The educator-role questionnaire was tested for validity and reliability, while affective-domain data were obtained from official documentation of dormitory assessments. Data were analyzed using simple linear regression. The results indicate that the role of dormitory educators significantly influences students’ affective development (Sig. = 0.000). The coefficient of determination (R² = 0.205) shows that 20.5% of the variance in the affective domain is explained by the educators’ role, while the remaining 79.5% is influenced by other factors beyond the scope of this study. The positive regression coefficient (B = 0.870) suggests that improvements in educator performance are associated with enhanced affective outcomes, particularly in discipline, religious attitude, responsibility, and social behavior. These findings reinforce the relevance of Social Learning Theory and the importance of educator modeling within residential education settings. The study concludes that dormitory educators serve as key agents in shaping students’ character in Islamic boarding schools. The novelty of this research lies in its quantitative empirical focus on the specific contribution of dormitory educators to affective development within a modern pesantren context. The findings provide an evidence-based foundation for strengthening character-building policies in residential Islamic education.